A104 A STUDY OF POST-INDUCTION INFLIXIMAB TROUGH LEVELS DEMONSTRATES MOST PEDIATRIC IBD PATIENTS ARE BEING UNDERDOSED. (26th February 2020) - Faytrouni, F; Harris, R; Lawrence, S; Russel, R
Abstract: Background: Infliximab (IFX) is widely used for induction and maintenance of remission in pediatric inflammatory bowel disease (PIBD). Post induction IFX trough levels are a predictor of clinical and biochemical remission at week 52. Aims: - evaluate the effectiveness of infliximab (IFX) induction regimens in attaining therapeutic post induction IFX trough levels in 2 PIBD cohorts. - investigate baseline laboratory values and patient factors as predictors of post-induction levels. Methods: 78 patients from Vancouver, Canada [Cohort 1 (C1) originator IFX; variable dose induction regimen] and 62 patients from Glasgow, Scotland [Cohort 2 (C2) replication cohort - biosimilar IFX; standard induction of 5mg/kg at 0, 2 and 6 weeks, with 8 weekly maintenance] were included in the study. Baseline characteristics and laboratory values from time of IFX initiation were recorded. Mann-Whitney U Testing was utilized to analyse the relationship between IFX trough levels and lab parameters. Results: The median pre-dose 4 trough in C1 & C2 was 4.25mg/L (IQR 7.8) and 1.85mg/L (IQR 3.38) respectively. In C1 patients who had a trough level <3mg/L pre-dose 4, 62% (20/32) had already had a dose adjustment documented. The IFX dose of 50% (39/78) of C1 patients and 65% (40/62) of C2 patients was escalated following the pre-dose 4 IFX level. TABLE 1 Baseline median albumin (Alb) was significantly lower and replicated in both cohorts in those with low pre-dose 4 IFX levels: IFX trough <0.8mg/L C1: Alb 30g/L vs 37.5g/L in IFX ≥0.8mg/L, p=0.002 C2: Alb 34.5g/L vs 37g/L in IFX ≥0.8mg/L, p=0.02 IFX trough <3.0mg/L C1:Alb 34.5g/L vs 38g/L in IFX ≥3.0mg/L, p= 0.05 C2:Alb 35g/L vs 37g/L in IFX ≥3.0mg/L, p=0.04 IFX trough <5.0mg/L C1:Alb 35g/L vs 39g/L in IFX ≥5.0mg/L, p=0.006 C2:Alb 35g/L vs 37g/L in IFX ≥5.0mg/L, p=0.45 In the combined cohort (C1 + 2), patients with baseline albumin ≤30g/L had significantly lower IFX levels pre-dose 4 than those with albumin >30g/L (1.4mg/L vs 3.55mg/L, p=0.0003). In patients with an albumin ≤30g/L, 23% (6/26) achieved a dose 4 trough level of ≥3.0mg/L, however only 1/6 patients received a standard induction regime meaning only 4% (1/26) of patients had a trough ≥3.0mg/L on standard treatment. Conclusions: Standard IFX induction regimen is ineffective in achieving relevant post-induction trough levels (>5 mg/L) in the majority of PIBD patients regardless of IFX type. We suggest that optimization of initial IFX prescribing based on baseline albumin (i.e. a higher dose given to patients with albumin < 30g/L) and subsequent levels will improve post-induction trough levels and consequently clinical outcomes for a greater proportion of patients. Funding Agencies: None